2009
DOI: 10.1159/000255161
|View full text |Cite
|
Sign up to set email alerts
|

High Faecal Calprotectin Levels in Healthy, Exclusively Breast-Fed Infants

Abstract: Background: Faecal calprotectin has been proposed as a sensitive marker for gastrointestinal inflammation in children and adults. High levels have been reported in healthy newborns and during the first months of life; the effect of the kind of feeding on the calprotectin concentration in stools is controversial. Objective: To evaluate faecal calprotectin values in healthy, exclusively breast-fed (BF) or formula-fed (FF) infants. Methods: Stool samples were obtained from 74 healthy infants (39 exclusively BF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
70
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 47 publications
5
70
2
7
Order By: Relevance
“…In this study, we observed no differences in hsCRP between the EF and SF groups. The breast-fed infants had significantly higher fecal calprotectin levels at baseline compared with the formula-fed infants, in line with previous findings (41). The high concentration of fecal calprotectin in young infants has been suggested to be due to increased intestinal permeability and transepithelial migration of neutrophils at this age, possibly related to the development of the intestinal microbiota (42).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we observed no differences in hsCRP between the EF and SF groups. The breast-fed infants had significantly higher fecal calprotectin levels at baseline compared with the formula-fed infants, in line with previous findings (41). The high concentration of fecal calprotectin in young infants has been suggested to be due to increased intestinal permeability and transepithelial migration of neutrophils at this age, possibly related to the development of the intestinal microbiota (42).…”
Section: Discussionsupporting
confidence: 88%
“…HBD2 should be dedicated to the protection of mucosal surfaces by preventing invasion of mucosa by intestinal microbes and promoting adaptive immune response. In contrast, a high calprotectin concentration reflects increased leukocyte migration through the gut mucosa as part of the intestinal hyperpermeability and mucosal immune stimulation of the gut-associated lymphoid tissue [27] .…”
Section: Discussionmentioning
confidence: 98%
“…Multiple biological functions of calprotectin have been shown in vitro and in vivo, such as involvement in the modulation of inflammatory processes and in the regulation of apoptosis, and a strong antimicrobial activity [2,4,10,11,13] . The immature intestinal mucosa of the fetus may allow a transepithelial migration of neutrophil granulocytes or macrophages into the gut lumen, resulting in higher calprotectin concentrations which might participate in the defense mechanisms in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…It is a cheap and noninvasive biomarker of intestinal inflammation and permeability, allowing the assessment of disease activity and monitoring of the response to treatment, highly valued by gastroenterologists for its specificity and sensitivity [1,2,[10][11][12] .…”
mentioning
confidence: 99%